Monitoring of the radio galaxy M 87 at Very High Energy with MAGIC during a low emission state between 2012 and 2015. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Arcaro, C.; Bangale, P.; Manganaro, M.; Mazin, D.; Colin, P.; Vovk, Ie.; Mannheim, K.; ,; Hada, K.; Jermak, H. E.; Madrid, J. P.; Massaro, F.; et al.
Abstract: We present the preliminary results from observing the nearby radio galaxy M 87 for 156 hours (between the years 2012 and 2015) with the MAGIC telescopes, which lead to a significant very high energy (VHE, E > 100 GeV) detection of the source in quiescent states each year. Our VHE analysis combined with quasi-simultaneous data at other energies (from gamma-rays, X-rays, optical and radio) provides a unique opportunity to study the source variability and its broadband spectral energy distribution, which is found to disfavour a one-zone synchrotron/synchrotron self-Compton model. Therefore, other alternative scenarios for the photon emission are explored. We also find that the VHE emission is compatible with being produced close to the source radio core as previous data already indicated. A detailed paper presenting full results of the observing campaign is in preparation.